Implementasi Pendidikan Karakter Pada Anak Usia Dini (Penelitian di Raudhatul Atfaal Nurul Ikhlas Depok) - Isep Djuanda; Hikmah Maryliana (Alim | Journal of Islamic Education, 2020)
This study aimed to perceive the implementation of character education for young learners in RA Nurul Ikhlas and discover the supporting factors and obstacles in implementing the program. Conducted using a qualitative method, the study resulted in the findings of definitions, concepts, characteristics, and phenomena on the implementation of character education for young learners in RA Nurul Ikhlas. The data was collected by observation, interview, and document analysis. The data analysis was conducted by applying Miles and Hubermen’ theory, which consisted of data reduction activity, data presentation, and conclusion drawing. The findings showed that: 1) Character education implementation in RA Nurul Ikhlas was conducted by scheduled activities, habits and merits, and learning by playing approach. Character education curriculum based on 9 character-pillars with center and circle learning model as well as various methods and evaluation: 2) the supporting factors for implementing character education are lesson plans integrated with character values, teachers’ competences, and school support. Meanwhile, the obstacles that hindered the implementation are as follows: a. the harmony between schools and homes in applying characters values are not favorable, b. less-conducive environment, c. uncontrolled or less-educated use of gadget, television, and internet